Pengaruh Profitabilitas Terhadap Harga Saham Pada Jakarta Islamic Index: Struktur Modal Sebagai Variabel Intervening - Ahmad Ulil Albab Al Umar; Yusvita Nena Arinta; Saiful Anwar; Anava Salsa Nur Savitri; Muhammad Ali Faisal (INVENTORY: JURNAL AKUNTANSI, 2020)
This study aims to analyze the profitability and capital structure of stock prices. The direct effect of profitability illustrated by ROA, ROE, NPM and EPS, and the capital structure proxied by DER on stock prices and the indirect effect of ROA, ROE, NPM, and EPS on stock prices through the Jakarta Islamic Index (JII) capital structure . The population in this study were 30 companies in the Jakarta Islamic Index (JII) for the 2015-2018 period. The results of this study found that ROA and NPM have a negative effect on stock prices. But NPM has a significant effect while ROA is not significant. ROE and EPS are both positive and significant effect on stock prices. The capital structure does not mediate the ROA and NPM variables but mediate the ROE and EPS variables on stock pricesKeyword : Profitability, Capital Structure, Stock Price